Modelling Malaysian gold prices using Box-Jenkins approach / Isnewati Ab Malek ... [et al.] - Ab Malek, Isnewati; Radin Nor Azam, Dewi Nur Farhani; Badrul Aidi, Dinie Syazwani; Sharim, Nur Syafiqah (2021)
Nowadays, gold is an excellent choice of investment for many reasons. It can be used as a hedge against inflation, the function of money and it will always be valuable because of rarity. The Malaysian Kijang Emas is Malaysia's official gold bullion coin and is minted by Malaysia's Royal Mint. This study aims to describe the trend of Kijang Emas and to find the best-fitted model of the ARIMA model in modelling volatile data. The general finding of this study is that the Kijang Emas prices indicate the presence of an upward trend, and no seasonality component exists in the data series. In estimating the parameters for the Box-Jenkins ARIMA model, Maximum Likelihood Estimation (MLE) is used. The modelling performance of ARIMA is evaluated by using the value of Akaike's Information Criterion (AIC), Bayesian Information Criterion (BIC), Root Mean Square Error (RMSE) and Mean Absolute Error (MAE). In terms of forecasting performance, ARIMA (2,1,1) is the more appropriate model for forecasting the future Kijang Emas prices because it has the smallest value of RMSE and MAE.